A POSSIBLE SOURCE FOR WILLIAM BLAKE'S "THE GREAT CODE OF ART". - Villalobos, John C. (English Language Notes)
Analyzes the line 'The Old and the New Testaments Are the Great Code of Art' from author William Blake. Identification of a mnemonic force in the line; Translation of author Robert Lowth on the text; Claim on the ability of Blake to examine a text with synecdochic imagination.